Achievements and Challenges in Software Reverse Engineering. - CANFORA, GERARDO; DI PENTA, MASSIMILIANO; CERULO, LUIGI (Communications of the ACM, 2011)
The article discusses the use of computer software reverse engineering to comprehend the abilities of a particular software application before engaging in modifications of it. Perspective is given on the need to modify software to adapt it to changing user requirements, changing business models, changing legislation, and technological innovations. A definition of software reverse engineering is excerpted from a paper authored by Chikofsky and Cross. A summary of the article's key insights is listed.